Nasal Delivery of D-Penicillamine Hydrogel Upregulates a Disintegrin and Metalloprotease 10 Expression via Melatonin Receptor 1 in Alzheimer’s Disease Models - Zhong, Manli; Kou, Hejia; Zhao, Pu; Zheng, Wei; Xu, He; Zhang, Xiaoyu; Lan, Wang; Guo, Chuang; Wang, Tao; Guo, Feng; Wang, Zhanyou; Gao, Huiling (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a type of neurodegenerative disease that is associated with the accumulation of amyloid plaques. Increasing non-amyloidogenic processing and/or manipulating amyloid precursor protein signaling could reduce AD amyloid pathology and cognitive impairment. D-penicillamine (D-Pen) is a water-soluble metal chelator and can reduce the aggregation of amyloid-β (Aβ) with metals in vitro. However, the potential mechanism of D-Pen for treating neurodegenerative disorders remains unexplored. In here, a novel type of chitosan-based hydrogel to carry D-Pen was designed and the characterization of D-Pen-CS/β-glycerophosphate hydrogel were tested by scanning electron microscopy and HPLC. Behaviour tests investigated the learning and memory levels of APP/PS1 mice treated through the D-Pen hydrogel nasal delivery. In vivo and in vitro findings showed that nasal delivery of D-Pen-CS/β-GP hydrogel had properly chelated metal ions that reduced Aβ deposition. Furthermore, D-Pen mainly regulated A disintegrin and metalloprotease 10 (ADAM10) expression via melatonin receptor 1 and the downstream PKA/ERK/CREB pathway. The present data demonstrated D-Pen significantly improved the cognitive ability of APP/PS1 mice and reduced Aβ generation through activating ADAM10 and accelerating non-amyloidogenic processing. Hence, these findings suggest that D-Pen could represent a promising agent for treating AD.